INDONESIAN MAKASSAR DIALECT EXPRESSIONS INTO ENGLISH - Yassir Mallapiang; Risman Wanci; Sujariati Sujariati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This research discussed about finding out Indonesian expressions that were embedded by Makassarese dialect and their translations culturally into English language. Non-standard Indonesian of Makassarese dialect is one of Indonesian dialects which is mostly communicated daily by Makassar citizens, one of Indonesian capital provinces; South Sulawesi. Using qualitative Corpus-Based and cultural translation approaches, the researcher had directly observed and identified one thousand six hundred fifty two Indonesian utterances. On the researcher’s observation and identification, the researcher found that those Indonesian utterances most of them had phonological, syntactical and semantical changes that deviated from standard Indonesian expressions. In finding out the cultural equivalences of those expressions into English, the researcher had found five thousand three hundred sixty six English utterances’ translation for the tabulated Indonesian expressions.